Estudios quimiotaxonómicos de Bursera (Burseraceae). II. Una especie nueva de origen híbrido de la Barranca de Tolantongo, estado de Hidalgo - Rzedowski, Jerzy; Ortiz, Evangelina (Instituto de Ecología, A.C., 1988)
Bursera medranoana sp.n. originates as a hybrid between B. morelensis Ramírez and B. schlechtendalii Engl., as can be proved by its morphological characters and its terpenoid composition. The three species ocurr together at the bottom of the Barranca de Tolantongo, east of Ixmiquilpan (state of Hidalgo, Mexico), where B. morelensis forms low forests on steep slopes. In a few localities, however, the density of trees of B. medranoana equals that of B. morelensis.